(untitled) (African Journal of Biomedical Research, 2021)
Pregnancy affects the mental, emotional, physical and psychological wellbeing of a woman and her unborn child. Although sexual intercourse during pregnancy is beneficial it is discouraged in many African countries for religious cultural reasons. Not enough is known about sexual activities during pregnancy among women of reproductive age in Nigeria. This study addressed this gap in knowledge. A total of 300 randomly selected women of reproductive age in Yemetu, Ibadan metropolis in South West Nigeria, were interviewed through a semi-structure interviewer administered questionnaire to determine their knowledge of the benefits of, attitude to, and sexual activities during pregnancy. Mean age of respondents was 32.1±7.7 years. The majority (69.9%) had adequate knowledge of benefits and positive attitude (68.7%) to sexual activity during pregnancy. A substantial percentage (91.5%) reportedly practiced sexual activities during pregnancy including vaginal intercourse (98.3%), kissing (38.5%), body fondling (34.4%) and masturbation (15.1%). Of 287 pregnant sexually active women 69.8% reportedly changed sexual behaviour during pregnancy; 25.3% reduced frequency of sex within the first trimester, 55.4% increased this activity in the second-third trimester and (25.3%) stopped during the birth week. The main reason for not having sexual activities during pregnancy was unavailability of their partners (33.3%). The predictors of sexual activities during pregnancy were; level of education, level of knowledge, source of knowledge and attitude. A large majority of women were adequately informed, held positive attitudes of the benefits and consequently participated in sexual activities during pregnancy. Health workers should continue to encourage women to practice sexual activities during pregnancy